2004
DOI: 10.1152/japplphysiol.00775.2003
|View full text |Cite
|
Sign up to set email alerts
|

Neuromuscular rehabilitation by treadmill running or electrical stimulation after peripheral nerve injury and repair

Abstract: Numerous studies have been devoted to the regeneration of the motor pathway toward a denervated muscle after nerve injury. However, the regeneration of sensory muscle endings after repair by self-anastomosis are little studied. In previous electrophysiological studies, our laboratory showed that the functional characteristics of tibialis anterior muscle afferents are differentially affected after injury and repair of the peroneal nerve with and without chronic electrostimulation. The present study focuses on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
78
2
7

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(88 citation statements)
references
References 50 publications
1
78
2
7
Order By: Relevance
“…Exercise, and in particular treadmill training, has been advocated for this purpose for patients with spinal cord injuries for some time (Edgerton, et al, 2004), but only recently has attention been devoted to its potential for treating peripheral nerve injuries. Marqueste et al (2004) found that treadmill training after common fibular nerve transection and repair results in better mechano-and metabosensitive afferent recovery in rats (Marqueste, et al, 2004). A more recent report showed a positive effect of treadmill training on axon regeneration in rats after sciatic nerve crush (Seo, et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Exercise, and in particular treadmill training, has been advocated for this purpose for patients with spinal cord injuries for some time (Edgerton, et al, 2004), but only recently has attention been devoted to its potential for treating peripheral nerve injuries. Marqueste et al (2004) found that treadmill training after common fibular nerve transection and repair results in better mechano-and metabosensitive afferent recovery in rats (Marqueste, et al, 2004). A more recent report showed a positive effect of treadmill training on axon regeneration in rats after sciatic nerve crush (Seo, et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Intensity was manipulated by altering treadmill speed. Continuous training has been used more extensively in animal exercise studies and has been applied in previous studies of exercise after peripheral nerve injury (Marqueste, et al, 2004, Seo, et al, 2006. However, the preferred approach to patterned running for rodents is brief intervals of high-intensity running interspersed with periods of rest (De Bono, et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several authors have shown beneficial results by using exercise, namely through greater budding and extension of the axons 12 , increased number of myelinated nerve fibers, 13,14 and improved functional recovery of the injured member [15][16][17] . There have been extensive discussions in the scientific community 18 regarding recommendations as per the type of exercise as well as its duration and intensity.…”
Section: Introductionmentioning
confidence: 99%
“…For this, low-frequency phased electrical stimulation 5 , chronic low-frequency electrostimulation 6 and physical exercise [7][8][9][10][11][12] have been used. Kinesiotherapy is prominent among physical therapy methods for rehabilitation following peripheral nerve injury.…”
Section: Introductionmentioning
confidence: 99%